Kreativitas Anak Usia 5-6 Tahun Melalui Pendidikan Keluarga : Studi Peran Orangtua di PAUD Permata Bangsa Mataram - Sasongko, Dara Ayu; Rizka, Muhammad Arief; Suharyani, Suharyani (Jurnal Paedagogy, 2022)
This study aims to describe the role of parents in increasing the development of early childhood creativity through family education at PAUD Permata Bangsa Mataram. The method used in this study is a mixed method. The population of this study was all parents of PAUD Permata Bangsa class TK B Jempong Mataram parents and the sample of this study amounted to 13 people using a population study. The research instrument used in this study was a questionnaire, observation and documentation. While the data analysis technique uses statistical analysis. The results of this study indicate that the level of the role of parents in developing the creativity of children aged 5-6 years through family education tends to be in the high category, as many as 88 with a percentage of 73%, supported by the results of observations of increased creativity of students who are in the high category, namely as much as 94 with a percentage of 80%. So based on the data of this study it can be concluded that the creativity of early childhood is very dependent on how the role of parents in providing family education to their children.